Proportional entropy of normal cardiac dynamic and with arrhythmia in the Intensive Care Unit - Javier Oswaldo Rodriguez; Signed Esperanza Prieto Bohórquez; Catalina Correa; Juan Pardo; Yolanda Soracipa; Ricardo Beltrán; Gydnea Aguirre; Laura Méndez (Revista de la Facultad de Ciencias Médicas de Córdoba, 2018)
Background: Based on the theory of probability and not equiprobable entropy ratios in the context of dynamical systems theory, a methodology for cardiac dynamic evaluation was developed. Objectives: To confirm the clinical applicability of the diagnostic methodology based on probability and entropy for patients with different types of arrhythmia assessing the degree of intensification in the ICU through its characteristic proportions. Methods: 80 Holter records from ICU diagnosed with arrhythmia and 20 normal were analyzed. Holter clinical findings were masked and were taken from them the maximum and minimum values of heart rate and total number of beats per minute to build the numerical attractor for each dynamics. Probability, entropy, S/k ratio, and proportions of entropy were evaluated, establishing its mathematical diagnosis and quantifying its severity level. Results: It was shown that the methodology difference in all cases normal of abnormal dynamics, obtaining a sensitivity and specificity of 100 % and Kappa coefficient of 1, showing that it is also possible to establish quantitatively the degree of exacerbation. Conclusions: The methodology developed is useful in clinical practice to correlate the severity of arrhythmias with physical and mathematical predictions of exacerbation.